Corporate Organizational Communication Strategy in Increasing Employee Motivation in Achieving Targets - Nanda Dwi Riskia; Hardi Fardiansyah; Eko Kuswoyo; Suherman Suherman; Geofakta Razali (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
BAF Bussan Auto Finance is a financial service provider company focusing on financing new motorbikes specifically for the Yamaha brand. Not only providing financing services for Yamaha brand motorcycles, Bussan Auto Finance also provides financing for car loans, electronic devices, gadgets, furniture, and agricultural machinery. Therefore, PT. BAF realizes there must be concrete steps to increase motivation and morale between employees and leaders. This study aims to determine organizational communication strategies for increasing the motivation and morale of Motor Yahama employees. Bussan Auto Finance (BAF) has the vision to become a leading and trusted finance company for customers, business partners, employees and the public. To realize this vision, Bussan Auto Finance has a mission to provide the best financial solutions for the welfare of society. The research method used is qualitative research with observations, interviews, and documentation conducted on Toyota Perintis Sales Department employees. The research results obtained by drawing this conclusion are the company's organizational communication strategy in increasing motivation and achieving good credit sales targets so that companies can achieve optimal or desired profits.